Fixed point teorems for multivalued maps via new auxiliary function - Ali, Muhammad Usman Usman; Vetro, Calogero (Nonlinear Analysis: Modelling and Control, 2017)
We introduce a contractive condition involving new auxiliary function and prove a fixed point theorem for closed multivalued maps on complete metric spaces. An example and an application to integral equation are given in support of our findings.